Utilizing alluvial deposits in Tamor River, Eastern Nepal: construction material suitability and extraction impact - Karna, Anand Kumar; Rawat, Bikram; Nepal, Sujan (Journal of Engineering Issues and Solutions, 2024)
The Tamor River, a tributary of the Koshi, has a potential to contribute construction raw materials for ongoing infrastructure development initiatives of the Koshi Province in the Eastern Nepal. However, due to the dynamic nature of river morphology and varying quality of alluvial deposits, it demands a rigorous testing of their suitability for construction purposes. This study aims to locate potential sites for material extraction, assess physical properties of available floodplain deposits, and evaluate potential adverse effects of extraction. Data were collected from field observations, structured interviews with local stakeholders, and consultation with experts/professionals. Field study encompassed an 85-kilometer stretch of the Tamor River, from Dovan to Mulghat. Results indicated the presence of alluvial deposits along the river’s entirety, with optimal extraction sites identified between Majhitar and Phalametar. Material available in the stretch from Limbunighat to Phalametar meets acceptable quality standards, albeit declining in the lower stretches of the study section. Adverse effects of extraction appear minimal and manageable with appropriate precautions. Consequently, it is recommended to extract materials for small-scale construction projects, ensuring adherence to safety protocols and confirming suitability through testing. Further investigations into Tamor River’s primary tributaries are advised to comprehensively assess resource potential.